Mucus and Ciliated Cells of Human Lung: Splitting Strategies for Particle Methods and 3D Stokes Flows - Chatelin, R.; Poncet, P.; Didier, A.; Murris-Espin, M.; Anne-Archard, D.; Thiriet, M. (Procedia IUTAM, 2015)
This proceeding is introducing a fractional step algorithm for diffusion-transport allowing computation of flows with sharp varia- tions of viscosity. This splitting also allows to perform transport with Lagrangian methods and diffusion with Eulerian methods, using hybrid grid-particle formulation. This splitting algorithm is globally second order. It is applied to computation of mucus mo- bility in human lungs, where epithelium ciliated cells are beating. A sufficient mobility is required to have healthy configurations. Our goal is to study the dependency of mucus mobility with respect to its viscosity in order to investigate mechanisms involved in pathologies such as cystic fibrosis.